1998
DOI: 10.1007/bf03339994
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of recovery from anorexia nervosa of a cohort patients re-evaluated on a long-term basis following intensive care

Abstract: The need to treat the acute onset of anorexia nervosa in a specialty unit is well known, but nevertheless, even "clinically recovered" patients show a high rate of relapse. The aim of our study was to re-evaluate various clinical (hemoglobin, transferrin, insulin-like growth factor I, TSH, PRL, gonadotropins and 17 beta-estradiol) and psychiatric [semistructured interview, Eating Disorder Inventory (EDI) Test] parameters in 19 female anorexic patients hospitalized in our department from 1983 to 1993 (with a 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…In outcome studies [1,3,5,6,19,[22][23][24][25][26][27], many different variables have been considered: sociodemographic elements (e.g. age, social class, schooling), anamnestic elements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In outcome studies [1,3,5,6,19,[22][23][24][25][26][27], many different variables have been considered: sociodemographic elements (e.g. age, social class, schooling), anamnestic elements (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Three-years after stable weight recovery, Bertoli et al [52] found that 8 women with previous AN remained at just over 85% of their ideal body weight, which was also significantly less than control women. Foppiani et al [100] also reported body weight to fall in the lower range of normal nine years after hospitalisation for AN, despite a general maintenance of body weight. Another long-term study that reported on body weight in recovered women, but did not include a control group, found the mean BMI to be 22 kg/m 2 after six years [46].…”
Section: Body Compositionmentioning
confidence: 93%
“…The AN group did show elevated fasting free fatty acid levels, possibly as a result of continued dieting behavior, and two of them met criteria for impaired glucose tolerance [148]. A median of nine years after hospitalisation for AN, Foppiani et al [100] did not find any abnormalities in thyroid, insulinlike growth factor, prolactin or gonadotropin measurements. Thus, from these few studies, it appears there are no residual effects of having AN on these endocrine systems.…”
Section: Endocrine and Metabolic Derangementsmentioning
confidence: 97%
“…Ce traitement se fait par voie veineuse. Il ne sera pas développé ici [1]. Le traitement de l'ostéoporose qui est la plus grave des complications chroniques nutritionnelles de l'anorexie mentale doit s'intégrer dans la prise en charge globale.…”
Section: Les Traitements Nutritionnels Et La Nutrition Artificielle :unclassified
“…Dans tous les cas l'évaluation des apports doit tenir compte de l'alimentation spontanée en plus des apports de la NE. Mais il est nécessaire d'être prudent, et le niveau de renutrition doit être d'autant plus bas et prudent que la dénutrition est sévère [1,33]. Dans ce cas, les apports ne doivent pas dépasser 10 kcal/kg les premiers jours de la renutrition d'un grand dénutri (IMC ≤ 11), sous couvert pendant trois à quatre jours d'une forte supplémentation vitaminique et phosphorée pour laquelle aucune recommandation précise ne fait l'unanimité.…”
Section: Modalités Et Conduite De La Nutrition Entéraleunclassified